Influence of Working Capital Management Practices on Financial Performance of Small and Medium Enterprises in Machakos Sub-County, Kenya - Nyakundi, Thomas; Ombuki, Charles; Zablon, Evusa; Jared, Ariemba (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2016)
Working capital can be considered as source of existence for all types of organizations, whether profit or non-profit organizations, therefore, it is a vital component for any profit making organizations for it influences operational level and sales volume. The purpose of this study was to assess the influence of Working Capital Management Practices on Financial Performance of SMEs in Machakos Sub-County, Kenya. This study was based on these objectives: assessment of the influence of cash management practices on financial performance, determination of the influence of receivables management practices on financial performance and the analysis of the extent to which inventory management practices influences financial performance of SMEs. The study adopted a cross-sectional survey research design which allowed the collection of primary quantitative data through structured questionnaires and interview methods. The target population was 159 Owners / Managers of SMEs trading in Machakos Sub-County. Random sampling technique was used to obtain a sample of 22 SMEs trading in Machakos Sub-County. The data was analyzed using both descriptive and inferential statistics.The findings of the study revealed that; working capital management practices were low amongst the SMEs, since majority had not adopted formal Working Capital Management Practices and there Financial Performance was on a low average. The study further revealed that SMEs financial performance was positively related to efficient cash management, efficient receivable management and efficient inventory management at 0.01 significance level. The coefficient of determination (R2) indicated that 0.507 or 50.7% of the variables in F.P could be explained by the changes ECM, ERM and EIM. This study concluded that WCMPs have an influence on the F.P of SMEs; therefore, there is need for SMEs owners / managers to embrace EWCMPs as a strategy to improve their F.P in order to survive in the turbulent business environment. This study corroborates extant literature findings that established a positive relationship between WCMP and F.P
Keywords: Working capital; Financial performance; Small and micro enterprises.